Pengaruh Return on Equity, Dividend Per Share, Earning Per Share Terhadap Harga Saham pada Sektor Keuangan dalam Indeks LQ-45 di Bursa Efek Indonesia (BEI) pada Tahun 2020-2024 - Rose, Thitania Silvaine; Firayanti, Yuni; Marhamah, Marhamah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study analyzes the impact of Return on Equity (ROE), Dividend Per Share (DPS), and Earnings Per Share (EPS) on the stock price movements of financial-sector companies listed in the LQ-45 Index on the Indonesia Stock Exchange over the 2020–2024 period. The LQ-45 Index was chosen for its high liquidity characteristics and representation of leading firms, making it a key benchmark for both institutional and retail investors. Research data consist of quarterly and annual financial statements obtained from the official Indonesia Stock Exchange (IDX) website and reputable financial data platforms. A purposive sampling technique was employed to select companies based on reporting consistency and complete data availability. Independent variables were measured using the ROE, DPS, and EPS financial ratios, while the dependent variable was the monthly average closing stock price. Data analysis was conducted via multiple linear regression using SPSS 30. The results yield the regression equation: Y = 5.031 – 5.616 ROE + 1.295 DPS + 0.166 EPS. The F-test indicates that the independent variables simultaneously have a significant effect on stock prices (p < 0.05). The t-test further reveals that DPS and EPS exert positive, significant impacts, whereas ROE has a negative, non-significant effect. These findings suggest that dividend policy and earnings-per-share growth are more determinant in driving the market value of financial-sector stocks. The study recommends incorporating liquidity and macroeconomic stability variables to broaden the analysis and achieve a more comprehensive perspective.